PENGGUNAAN MODEL PEMBELAJARAN INQUIRY PADA MATA PELAJARAN PAI DI SMAN 1 BANUHAMPU - Ridho Aulia; Charles Charles; Wedra Aprison; Arifmiboy Arifmiboy (KOLONI, 2022)
This research is motivated by the phenomenon of the author's interview about the use of the Inqury learning model with the aim of making students become active in participating in learning. However, there are some steps that are left behind and there is no group cooperation in learning. The purpose of this study was to find out how PAI teachers used the Inquiry learning model in class X PAI learning at SMAN 1 Banuhampu. This research use desciptive qualitative approach. The collection of research data obtained from interviews. This research was conducted by taking key informants of Islamic Religious Education teachers, and supporting informants for class X students, and the principal of SMAN 1 Banuhampu. The data analysis technique that the author uses is data reduction to ensure the validity of this study, the author uses data triangulation, and draws conclusions. From this research, there are steps in the inquiry learning model, namely orientation, formulating problems, formulating hypotheses, testing hypotheses, concluding, and drawing conclusions. The use of the inquiry model has been implemented by the teacher well. This can be shown in the use of the inquiry model on the material of the Prophet's da'wah strategy in Medina, but there are several steps left by the teacher, no orders to challenge students, namely with other pairs, and no conclusions from the questions in the presentation results through the inquiry model. Keywords: Using the Inquiry Learning Model, PAI Learning